Application of Hyaluronic Acid for Treatment of Interdental Papillary Deficiency: A Systematic Review and Meta-Analysis - Jowel Makdisi; solmaz akbari; Farid Zayeri; Hoori AslRoosta; Siamak Yaghobee (Frontiers in Dentistry, 2023)
Objectives: The focused question of this systematic review was “does hyaluronic acid (HA) injection in areas of interdental papillary deficiency reduce black triangles?”